2020
DOI: 10.1038/s41419-020-2525-x
|View full text |Cite|
|
Sign up to set email alerts
|

FTSJ1 regulates tRNA 2ʹ-O-methyladenosine modification and suppresses the malignancy of NSCLC via inhibiting DRAM1 expression

Abstract: Non-small cell lung cancer (NSCLC) is the leading cause of cancer mortality worldwide. The mechanisms underlying NSCLC tumorigenesis are incompletely understood. Transfer RNA (tRNA) modification is emerging as a novel regulatory mechanism for carcinogenesis. However, the role of tRNA modification in NSCLC remains obscure. In this study, HPLC/MS assay was used to quantify tRNA modification levels in NSCLC tissues and cells. tRNA-modifying enzyme genes were identified by comparative genomics and validated by qRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 43 publications
(69 reference statements)
2
26
0
Order By: Relevance
“…Consistently with the well known FTSJ1 implication in ID and more recently in cancer (Holzer et al 2019; Q. He et al 2020), we found 36 differentially expressed miRNAs, most of which were already associated with brain diseases and functioning and/or cancer development. The most prevalent associated cancer types were the ones related to the brain tissues.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Consistently with the well known FTSJ1 implication in ID and more recently in cancer (Holzer et al 2019; Q. He et al 2020), we found 36 differentially expressed miRNAs, most of which were already associated with brain diseases and functioning and/or cancer development. The most prevalent associated cancer types were the ones related to the brain tissues.…”
Section: Discussionsupporting
confidence: 86%
“…As FTSJ1 mutated LCLs originated from patients affected by NSXLID and regarding the recent link of FTSJ1 implication in cancer control pathways (Holzer et al 2019; Q. He et al 2020) and the cancer related miRNAs deregulated in patients’ LCLs (Figure. 2b), we selected representative and disease-relevant deregulated mRNAs obtained in the RNAseq analysis based on their fold change level of expression and related involvement in brain or cancer diseases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In their metabolic process, defects in any step may cause various human diseases [82][83][84] . For example, the tRNAmodifying enzyme FTSJ1 was down-regulated in nonsmall cell lung cancer (NSCLC) tissues 85 . Importantly, FTSJ1 inhibited the growth of NSCLC cells by reducing the expression of DNA damage-regulated autophagy modulator 1.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%